« Il faut éduquer les enfants... » L'idéologie de l'éducation en question - Audidière, Sophie; Janvier, Antoine (La croisée des chemins, 2022)
The sentence "children have to be educated..." seems all at once like a foregone conclusion, an injunction and an ideal. It seems obvious to adhere to what seems to be an anthropological invariant. However, this work proposes another perspective based on philosophical and historical studies of two major periods: a long nineteenth century tormented by the Revolution and emancipation, which gave birth to the central figure of the school, and a twentieth century moulded by extreme violence and concern about the human being. Focusing on theoretical and practical experiments that reveal the contradictions or flaws of educational apparatuses, this book engages in a critical philosophical approach on the "ideology of education" which has commanded, for two or three centuries at least, our ways of learning, of socialising, of helping children grow up and forming them in determined institutions (the family and the school above all) and according to precise representations and categories (the category of childhood, in the first place). This is the 'ideology of education' that we purport here to reflect, problematise and question.